Helminth Allergens, Parasite-Specific IgE, and Its Protective Role in Human Immunity - Fitzsimmons, Colin M.; Falcone, Franco H.; Dunne, David W. (Frontiers in Immunology, 2014)
The Th2 immune response, culminating in eosinophilia and IgE production, is not only characteristic of allergy but also of infection by parasitic worms (helminths). Anti-parasite IgE has been associated with immunity against a range of helminth infections and many believe that IgE and its receptors evolved to help counter metazoan parasites. Allergens (IgE-antigens) are present in only a small minority of protein families and known IgE targets in helminths belong to these same families (e.g. EF-hand proteins, tropomyosin, and PR-1 proteins). During some helminth infection, especially with the well adapted hookworm, the Th2 response is moderated by parasite-expressed molecules. This has been associated with reduced allergy in helminth endemic areas and worm infection or products have been proposed as treatments for allergic conditions. However some infections (especially Ascaris) are associated with increased allergy and this has been linked to cross-reactivity between worm proteins (e.g., tropomyosins) and highly similar molecules in dust mites and insects. The overlap between allergy and helminth infection is best illustrated in Anisakis simplex, a nematode that when consumed in under-cooked fish can be both an infective helminth and a food allergen. Nearly 20 molecular allergens have been isolated from this species, including tropomyosin (Ani s3) and the EF-hand protein, Ani s troponin. In this review, we highlight aspects of the biology and biochemistry of helminths that may have influenced the evolution of the IgE response. We compare dominant IgE antigens in worms with clinically important environmental allergens and suggest that arrays of such molecules will provide important information on anti-worm immunity as well as allergy.